The Trabecular Bone Score as a Predictor for Thalassemia-Induced Vertebral Fractures in Northeastern Thailand. (22nd July 2020) - Teawtrakul, Nattiya; Chukanhom, Sukanya; Charoensri, Suranut; Somboonporn, Charoonsak; Pongchaiyakul, Chatlert
Abstract : Introduction . Thalassemia bone disease is one of the disease-related complications in patients with thalassemia. Prevalence of fractures and the role of a trabecular bone score (TBS) as a predictive factor for fractures were evaluated in patients with thalassemia. Methods . A cross-sectional study was conducted in patients with thalassemia aged ≥18 years at Srinagarind Hospital, Khon Kaen University, Thailand. A lateral thoracolumbar radiograph and bone mineral density (BMD) at the lumbar spine and hip, as well as the TBS measured by dual-energy X-ray absorptiometry (DXA), were evaluated in all patients. Results . Among 86 patients, 14 patients were found to have radiographic vertebral fracture yielding a prevalence of 16.3%. All patients who had fractures were β -thalassemia/Hb E. Combined low BMD and TBS at lumbar spines and a presence of endocrinopathies were significantly associated with vertebral fractures. Conclusions . The prevalence of vertebral fractures in patients with thalassemia was not uncommon. A combined low BMD and TBS and a presence of endocrinopathies were associated with vertebral fractures. These findings suggested that BMD testing and TBS measurement have a clinical implication as a screening tool for evaluating the risk of vertebral fractures in thalassemic patients, particularly in β -thalassemia/Hb E who have endocrinopathies.